Hackathons as Inclusive Spaces for Prototyping Software in Open Social Innovation with NGOs - Gama, Kiev; Valenca, George; Estelle Marques Laurendon, Candy; Nasidi Marques, Ajo; Eduardo Ramos, Luis; Amaral, Ravena; Maria Dubeux Lopes Barros, Clarissa; Xavier, Guilherme (IEEE/ACM International Conference on Software Engineering: Software Engineering in Society (Online), 2023)
Non-governmental Organizations (NGOs) usually have limited resources that prevent them from investing in software-based innovation. Sometimes hackathons are used as a resource to crowdsource software for NGOs, but often the resulting projects are not usable or not carried on. These events are not seen as a good option in Software Engineering for social good (i.e., software focused on social change) since they are too short to allow an understanding of the social context of the target institution. Taking that limitation into account, after performing 6 months of ethnography to understand the social context of an NGO, by identifying user needs and eliciting requirements, we organized an inclusive hackathon to address two specific challenges identified in that organization. This paper presents an experience report in the context of an interdisciplinary project with researchers from the Psychology, Design, and Computer Science domains, where the goal is to propose and apply an Open Social Innovation process focused on digital innovative solutions in the context of an NGO from Brazil that supports socially vulnerable people living with HIV/AIDS.